Utility of fuzzy set Qualitative Comparative Analysis (fsQCA) methodology to identify causal relations conducting to cooperative failure - Pozuelo Campillo, José; Romero Martínez, Mariano; Carmona Ibáñez, Pedro (CIRIEC-España, 2023)
This study focuses on the search for the causes, or combination of circumstances, that lead to business failure processes. There is renewed interest in this subject due to the adverse consequences that the recent economic crisis has caused in the business world. A fuzzy set Qualitative Comparative Analysis (fsQCA) is thus carried out to identify the combination of financial ratios that points to situations of financial difficulty. The study centres on the cooperative sector, represented by a sample of 56 companies holding this legal status, belonging to various different productive sectors. The results obtained, and confirmed through a number of different robustness tests, reveal the presence of sufficient conditions comprising combinations of variables reflecting high indebtedness, low liquidity, low solvency and small firm size, representing a scenario that would be sufficient for an entity to face business continuity problems. Thanks to its ability to identify combinations of variables that warn of business failure, as well as its ease of interpretability, the fsQCA technique can be extremely useful for business management and the identification of business failure situations.